Posiadanie praw publicznych oraz posiadanie praw wyborczych jako przesłanki czynnego prawa wyborczego w Rzeczypospolitej Polskiej - Biłgorajski, Artur (Polityka i Społeczeństwo, 2021)
The aim of the study is to analyze and evaluate the two conditions of the active right to vote in the Republic of Poland, namely: having public rights and having the right to vote; and also to determine their mutual relations. This topic is worth considering for at least two reasons. Firstly, as a rule the representatives of the science of constitutional law do not deal with those conditions, assuming that it is the domain of specialists in other areas of law, especially in substantive criminal law. Secondly, those conditions are very often identified with each other. This is an obvious mistake, because the institutions of “deprivation of public rights", and "deprivation of the right to vote", which are related to the conditions discussed above, differ in the following areas: the legal basis; the nature of the sanctions; objective scope; subjective scope; conditions of their application; the authorities empowered to use them; the period of time during which they can be ordered.